GAMBARAN KUALITAS HIDUP PASIEN CEDERA KEPALA PASCA OPERASI PERIODE JANUARI 2012 - DESEMBER 2013 DI RSUP PROF. DR. R. D. KANDOU MANADO - Zwingly, Patrick; Oley, Maximillian Ch.; Limpeleh, H. P. (e-CliniC, 2015)
Abstract: Traumatic brain injury is a major global problem. Global incident average in urban areas ranged from 108 to 332 new cases admitted to the hospital per 100,000 population per year. About 39% of patients with severe brain trauma died due to injuries, and 60% had low Glasgow Outcome Scale (GCS). Neurosurgical surgery decreased the incidence of death and injury due to head trauma from 72 to 25%. However, patients still show significant disability after completion of therapy. Disability could manifest in the form of physical, mental, and/or behavior disability. This was a descriptive study with a cross-sectional design by using a questionnaire. This study aimed to obtain the quality of life of patients with head injury in post-operative period from January 2012 - December 31, 2013 in Prof. R. D. Kandou Hopital Manado. The results showed that most respondents were male (61.3%), aged 11-20 years (48.6%). Most respondents lived at Malalayang (19.4%). The most frequent head injuries were mild head injuries (74.2%). The final states of the patients (GOS) were: good recovery 58.1% and moderate disability 41.9%. Patients with GCS mild, moderate, or good recovery disability were 3.2% each. Patients with GCS were mostly good recovery (48.4%). Most patients with severe GCS experienced moderate disability (12.9%). Characteristics of patient satisfaction were satisfied 54.8% and not satisfied 45.2%. Relationship of satisfaction level with GOS was as follows: most satisfied patients had good recovery (35.5%), where as most not-satisfied patients had moderate disability (29.0%).Keywords: head injury, post craniotomy, patient satisfactionAbstrak: Kerusakan otak traumatik merupakan masalah global utama. Insiden rata-rata di perkotaan secara global berkisar dari 108 sampai 332 kasus baru yang masuk rumah sakit per 100.000 populasi per tahun. Rata-rata 39% pasien-pasien dengan trauma otak berat meninggal karena cedera, dan 60% memiliki Glasgow Outcome Scale (GCS) yang rendah. Tindakan operasi bedah saraf menurunkan insiden kematian dan cedera akibat trauma kepala dari 72 sampai 25%. Meski demikian, pasien-pasien tetap menunjukkan kecacatan yang nyata sesudah menyelesaikan terapi, baik berupa cacat fisik, mental, dan/atau perilaku. Penelitian ini bertujuan untuk melihat gambaran kualitas hidup pasien cedera kepala pasca operasi periode Januari 2012-Desember 2013 di RSUP. Prof. Dr. R. D. Kandou Manado. Hasil penelitian menunjukkan responden terbanyak ialah laki-laki (61,3%), usia terbanyak 11-20 tahun (48,6%), alamat responden terbanyak di Malalayang (19,4%). Cedera kepala terbanyak ialah cedera kepala sedang sebesar 74,2%. Keadaan akhir pasien (GOS), good recovery sebesar 58,1%, sedangkan moderate disability 41,9%. Pasien dengan GCS ringan, moderate dissability dan good recovery masing-masing sebesar 3,2%. Pasien dengan GCS sedang paling banyak good recovery yaitu 48,4%. Pasien dengan GCS berat paling banyak mengalami moderate dissability yaitu 12,9%. Karakteristik kepuasan pasien diperoleh puas sebesar 54,8% sedangkan yang tidak puas 45,2%. Hubungan tingkat kepuasan dengan GOS, yang puas ter banyak pasien yang good recovery yaitu 35,5%, sedangkan yang tidak puas terbanyak moderate dissability yaitu 29,0%.Kata kunci: cedera kepala, pasca kraniotomi, kepuasan pasien.